Cellular and Molecular Mechanisms Mediating Methylmercury Neurotoxicity and Neuroinflammation - Novo, João P. (2021)
Methylmercury (MeHg) toxicity is a major environmental concern. In the aquatic reservoir, MeHg bioaccumulates along the food chain until it is consumed by riverine populations. There has been much interest in the neurotoxicity of MeHg due to recent environmental disasters. Studies have also addressed the implications of long-term MeHg exposure for humans. The central nervous system is particularly susceptible to the deleterious effects of MeHg, as evidenced by clinical symptoms and histopathological changes in poisoned humans. In vitro and in vivo studies have been crucial in deciphering the molecular mechanisms underlying MeHg-induced neurotoxicity. A collection of cellular and molecular alterations including cytokine release, oxidative stress, mitochondrial dysfunction, Ca2+ and glutamate dyshomeostasis, and cell death mechanisms are important consequences of brain cells exposure to MeHg. The purpose of this review is to organize an overview of the mercury cycle and MeHg poisoning events and to summarize data from cellular, animal, and human studies focusing on MeHg effects in neurons and glial cells. This review proposes an up-to-date compendium that will serve as a starting point for further studies and a consultation reference of published studies.